The effect of long germination on the levels and types of non-enzymatic antioxidants in red kidney bean sprouts - Winarsi, Hery; Bestari, Yudhanti Putri; Masluki, Nisa Ilmi Lulu; Septiana, Aisyah Tri (Proceeding ICMA-SURE; Vol 1 No 1 (2021): Proceeding ICMA-SUREDO - 10.20884/2.procicma.2021.1.1.4417, 2021)
This study aims to explore the content of several types of non-enzymatic antioxidants in red kidney beans sprout based on duration germination. The complete randomized design study was carried out by red kidney beans sprout with germination duration variables of 0, 10, 20, and 30 hours. Red kidney bean sprouts are blended with water 8 times the amount, then filtered, so that red kidney bean sprouts extract is obtained. The phenolic content determinate using the Folin-Ciocalteu method; vitamin C testing using Iodometry; and fiber content by the proximate method. Data were analyzed using ANOVA, followed by the DMRT test if there was any significance with an error rate of 5%. The selection of products with the highest antioxidant content uses the effectiveness index test. The duration of germination increased the content of phenolic antioxidant (P <0.05), vitamin C (P <0.05), and fiber (P <0.05). Red kidney bean sprouts resulting from germination for 30 hours have the highest content antioxidants of phenolic, vitamin C, and fiber, respectively 583.85 mg GAE/L, 23.14 mg/100 mL, and 6.75%. Red kidney bean sprouts can be used as an ingredient of antioxidant-rich products that are useful for the prevention of degenerative diseases